HEPARIN-INDUCED THROMBOCYTOPENIA (REVIEW) - S. A. Vasiliev; L. A. Gorgidze; T. N. Moiseeva; L. S. Al'-Radi; N. I. Zozulya; M. A. Sokolova; A. V. Mazurov («REMEDIUM GROUP» Ltd., 2019)
Heparin-induced thrombocytopenia (HIT) is a serious and potentially life-threatening side effect of heparinotherapy. It is an antibody-mediated process that causes platelet activation, increases the procoagulant characteristics of the blood and, as a result, endangering limbs and life-threatening thrombosis. Venous thrombosis is more common than arterial thrombosis, especially deep vein thrombosis of the lower limbs and pulmonary artery thrombosis. Mortality from complications of heparinotherapy occurs with a frequency of 20-30 % of cases. Diagnosis of HIT is difficult. Such basic symptoms as thrombocytopenia and thrombosis are extremely non-specific and may be present in cancer patients and patients with cardiosurgical pathologies without the impact of heparin. Women are twice as likely to have HIT as men. This review describes pathogenesis, clinical features, modern diagnostic methods, risk factors for the emergence of this formidable complication of heparinotherapy, gives an overview of the most frequent use of drugs for the treatment of HIT, and gives modern clinical recommendations for different groups of patients.